Photonuclear production of ⁹⁹Mo/ ⁹⁹ᵐТс-generator with using effect Szilard-Chalmers and electrolysis method - Dikiy, N.P.; Layshko, Yu.V.; Medvedeva, E.P.; Medvedev, D.V.; Uvarov, V.L. (Problems of Atomic Science and Technology, 2022)
The possibility of photonuclear production of ⁹⁹Mo medical radioisotope using recoil nuclei of molybdenite nanoparticles from reaction ¹⁰⁰Mo(γ,n)⁹⁹Mo was investigated. The enrichment of radioactive isotopes is carried out by the effect of Szilard-Chalmers. Molybdenite nanoparticles were irradiated by bremsstrahlung with Emax = 39 MeV. The recoil nuclei of ⁹⁹Mo are separated by electrolysis. The yield of ⁹⁹Mo from the extractable phase amounted to ∼3%. This technology will allow producing 0.8 GBq/g of ⁹⁹ᵐTc with high specific activity per day. Key words: linear electron accelerator, photonuclear production, electrolysis, specific activity, recoil nuclei, molybdenite nano-particles. Досліджена можливість фотоядерного виробництва медичного ізотопу ⁹⁹Mo з використанням ядер віддачі наночастинок молібденіту з реакції ¹⁰⁰Mo(γ,n)⁹⁹Mo. Збагачення радіоактивними ізотопами здійснюється за реакції Сціларда-Чалмерса. Наночастинки молібденіту були опроміненні гальмівним випромінюванням на ЛПЕ з Emax = 39 МеВ. Ядра віддачі ⁹⁹Mo були виділені методом електролізу. Вихід ⁹⁹Mo з фази екстракції становив ∼3%. Ця технологія дозволить виробляти ∼ 0,8 ГБк/г ⁹⁹ᵐTc з високою питомою активністю за добу.